The barriers and ways for development of Siberia's regions with limited transport accessibility - Leonid Bezrukov (European Regional Science Association (ERSA), 2012)
Areas with limited transport accessibility are considered to mean territories lacking year-round roads and routes, such as railroads, motor roads, sea routes, and inland waterways. Siberia, as Russia's largest macroregion, has within its boundaries huge territories difficult of access, where only seasonal waterways and winter motor roads, and also expensive air transport are available. The socioeconomic state of the Siberian areas with limited transport accessibility is under a negative influence of two transport-economic barriers simultaneously. The presence of the former barrier is characteristic for the whole of Siberia, including the zone serviced by railroads and all-the-year-round motor roads. The operation of this barrier is associated with the landlocked macrolocation of Siberia, and with the huge and expensive distances which have to be traveled when transporting cargo and passengers to the leading centers and sea ports of Russia and the world at large (and, accordingly, vice versa). The chief point is that there is still a significant difference between land transport tariffs, on the one hand, and economical sea transportation rates, on the other. Therefore, in landlocked regions, and in Siberia in particular, the high transport expenses continue to have an unfavorable influence on economic efficiency and remain a severe obstacle to the entry into the remote markets. The second barrier arises directly because of lack of year-round communications, and its operation is characteristic precisely for areas with limited transport accessibility doomed to drag out a backward socioeconomic existence or bear sky-rocketed transport expenses. Compared with the belt along the railroads, the transport expenses in areas without railroads increase several times, which was established through our estimation of cost for the transport-geographical location (TGL) of Siberia's administrative districts. Districts with a particularly disadvantageous TGL are represented by the most backward and peripheral territories of the Sakha Republic, Krasnoyarsk Territory, Irkutsk Oblast, Tyva Republic, and some other Siberian subjects of the Russian Federation which are distinguished for an exceptionally sparse network of human settlements, a total lack of good roads, and for extensive kinds of economy. The broad-scale construction of new railroads and all-the-year-round motor roads, as planned by the "Transport strategy of the Russian federation into the year 2030", would radically change the situation for the better. According to our assessment, the implementation of the aforementioned "Strategy" would lead to a reduction in transport expenses and to an improvement in TGL of about 100 areas of Siberia, which would create favorable possibilities for their full-fledged socioeconomic development.
Keywords: 330